From Status to Contract? A Macrohistory from Early-Modern English Caselaw and Print Culture - Peter Grajzl; Peter Murrell (CESifo GmbH, 2024)
Most modernization or development theories that incorporate law emphasize a growth in the scope of individual choice as law becomes impartial, relevant to all. An early expression of this conceptualization was Henry Maine's (1822-1888) celebrated dictum that progressive societies move from status to contract. We conduct an inquiry into Maine's conjecture using machine-learning applied to two early-modern English corpora, on caselaw and print culture. We train word embeddings on each corpus and produce time series of emphases on contract, status, and contract versus status. Only caselaw exhibits an increasing emphasis on contract versus status, and even that trend is discernible only before the Civil War. Thus, our results can be interpreted as showing that development theories emphasizing the widening of individual choice do not characterize England in the century prior to the Industrial Revolution. After 1660, caselaw trends reflect the increasing importance of equity compared to common-law, with equity increasingly emphasizing status. This effect is particularly evident in the status-oriented family and inheritance law. In print culture, religion consistently emphasizes contract over status while politics exhibits a downward-trending emphasis on contract versus status. VAR estimates reveal that the applicable ideas in caselaw and print culture coevolved.
Keywords: K10; Z10; N00; P10; C80; 330; contract versus status; Henry Maine; early-modern England; machine learning; caselaw; print culture